RECORDIT and capacity utilization: Real Cost Reduction of Door-To-Door intermodal Transport - Weibel, Tim Gustav; Henriques, Michael (Proceedings from the Annual Transport Conference at Aalborg University, 2002)
The recent White Paper of the EC on the revision of the Common Transport Policy 1 devotes a special attention to intermodal freight transport services. In its section: “Linking up the modes of transport”, the White Paper advocates a number of technical, economic and organisational innovations that directly aim at increasing the attractiveness of intermodal solutions. On the other hand, and no less importantly, many other measures and actions proposed by the White Paper, although they do not target intermodal freight transport as such, are immediately relevant to the general objective of promoting intermodality. Specifically: the revitalisation of European railways (through radical increases in efficiency and the eventual establishment of a dedicated freight network), the introduction of an adequate system of transport infrastructure charging, the generalised improvement of the quality of transport services, are all fundamental prerequisites to achieve a higher degree of competitiveness in the intermodal freight sector.